Cost Analysis in Higher Education of Tribhuvan University - Paudel, Minraj (Tribhuvan University Journal, 2020)
The study analyzes the direct private and social cost of higher education in Tribhuvan University (TU) of Nepal. Post-positivist approach and survey methods with descriptive and explanatory design have been used, and both qualitative and quantitative data were collected from closed and semi-closed questionnaires. Simple random, stratified and purposive sampling techniques have been used. After the study, it is found that girls are more expensive than boys by 2.52 percent in the case of direct private non-institutional educational costs. Furthermore, if any student wants to study the master level under TU, s/he must invest NRs3,08,858, NRs 3,43,170, NRs 3,43,370, NRs 3,75,843, NRs 5,18,477 and NRs 4,57,695 to get the degree from central department of Education, Nepali, English, Management, Zoology and Chemistry respectively as direct private cost up to complete this educational cycle. Except capital cost, the government of Nepal has burdened 61.82 percent and 38.18 percent by the household of higher education in TU, Nepal.